Effect of reproductive ageing on pregnant mouse uterus and cervix. (8th February 2017) - Patel, Rima; Moffatt, James D.; Mourmoura, Evangelia; Demaison, Luc; Seed, Paul T.; Poston, Lucilla; Tribe, Rachel M.
Abstract : Key points: Older pregnant women have a greater risk of operative delivery, still birth and post‐term induction. This suggests that maternal age can influence the timing of birth and processes of parturition. We have found that increasing maternal age in C57BL/6J mice is associated with prolongation of gestation and length of labour. Older pregnant mice also had delayed progesterone withdrawal and impaired myometrial function. Uterine ageing and labour dysfunction should be investigated further in older primigravid women. Abstract: Advanced maternal age (≥35 years) is associated with increased rates of operative delivery, stillbirth and post‐term labour induction. The physiological causes remain uncertain, although impaired myometrial function has been implicated. To investigate the hypothesis that maternal age directly influences successful parturition, we assessed the timing of birth and fetal outcome in pregnant C57BL/6J mice at 3 months (young) and 5 months (intermediate) vs . 8 months (older) of age using infrared video recording. Serum progesterone profiles, myometrium and cervix function, and mitochondrial electron transport chain complex enzymatic activities were also examined. Older pregnant mice had a longer mean gestation and labour duration ( P < 0.001), as well as reduced litter size ( P < 0.01) vs . 3‐month‐old mice. Older mice did not exhibit the same decline in serum progesterone concentrations as younger mice. Cervical tissues from older mice were more distensible than younger mice ( P < 0.05). Oxytocin receptor and connexin‐43 mRNA expression were reduced in the myometrium from 8‐month‐old vs . 3‐month‐old mice ( P < 0.05 and P < 0.01 respectively) in tandem with more frequent but shorter duration spontaneous myometrial contractions ( P < 0.05) and an attenuated contractile response to oxytocin. Myometrial mitochondrial copy number was reduced in older mice, although there were no age‐induced changes to the enzymatic activities of the mitochondrial electron transport chain complexes. In conclusion, 8‐month‐old mice provide a useful model of reproductive ageing. The present study has identified potential causes of labour dysfunction amenable to investigation in older primigravid women. Key points: Older pregnant women have a greater risk of operative delivery, still birth and post‐term induction. This suggests that maternal age can influence the timing of birth and processes of parturition. We have found that increasing maternal age in C57BL/6J mice is associated with prolongation of gestation and length of labour. Older pregnant mice also had delayed progesterone withdrawal and impaired myometrial function. Uterine ageing and labour dysfunction should be investigated further in older primigravid women.